Sosialisasi Penggunaan Artificial Intelligence untuk Anak-Anak Komunitas Jendela Jakarta di Manggarai Utara - Izra Noor Zahara Aliya; Cendana Putri Aulia; Moh. Azzam Priyanto; Yanuar Hakam Rosyadi A; Dhian Satria Yudha Kartika (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2024)
This Community Service activity aims to socialize the use of Artificial Intelligence (AI) to children aged 6-13 years in the Window Community, Jakarta, North Manggarai Branch with an exciting and interactive approach. Through the topic